MENGENAL MUSNAD AHMAD IBN HANBAL - Rustina N (IAIN Ambon, 2013)
The existence of hadith is very urgent in Islamic law, because hadisth is the second source of Islamic law teachings. In this regard an hadith is worthy made as the source of Islamic law if it meets the validity level both sanad and matan. The validity level of hadith is most varied depending on the writer. One of the Hadith Book is Musnad Ahmad ibn Hanbal. From the result of study is recognized that there is authentic quality and some are dhaif (weak) hadiths in the Musnad Ahmad bin Hanbal The existence of the hadith dhaif in Musnad Ahmad was influenced by the attitudes and his views that more preceding the weak hadith than opinions or ra'yu. He also allows the use of hadith dhaif as basis in the problem of fadhai ‘amal or basic on the benefit and utility of a practice. Keywords: Musnad Ahmad ibn Hanbal, validity level of hadith